2007
DOI: 10.1016/j.electstud.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Consequences of low turnout

Abstract: Low electoral turnout has become common in many countries. Whether this is a problem for a democracy depends ondamong other thingsdwhether higher turnout would have made other parties more relevant. This introductory article discusses the findings and approaches of previous work on this question and summarizes the findings of the work published in this issue. The various articles, despite using different approaches, looking at different countries and different types of election, all show that any bias in elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 54 publications
(47 reference statements)
2
48
1
3
Order By: Relevance
“…The most straightforward explanation is that citizens may change their median position, or there may be differential turnout between groups of voters which will change the aggregate images of parties. We know that low turnout has a range of political consequences (Lutz and Marsh 2007), so it follows that turnout may influence the left-right position of the electorate as well. A variant of this explanation suggests that if voters change their images of the parties, perhaps in response to changes in leadership, this will in turn alter their median position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most straightforward explanation is that citizens may change their median position, or there may be differential turnout between groups of voters which will change the aggregate images of parties. We know that low turnout has a range of political consequences (Lutz and Marsh 2007), so it follows that turnout may influence the left-right position of the electorate as well. A variant of this explanation suggests that if voters change their images of the parties, perhaps in response to changes in leadership, this will in turn alter their median position.…”
Section: Resultsmentioning
confidence: 99%
“…More generally yet, Lutz and Marsh (2007) reviewed a number of articles that tried to estimate turnout effects, in different countries, in different periods, and in different kinds of elections, and concluded that "…turnout does not matter a great deal." We may thus wonder why it is that turnout effects vAn der eI j k / s c hm Itt / sAPI r / 196 are so insignificant while in principle they could be quite important.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Conventional answers to the question of whether the counterfactual participation of nonvoters would have changed an election result make reference to the change in the division of the vote resulting from adding the putative preferences of nonvoters to those of actual voters (see, e.g., Brunell and DiNardo 2004;Franklin 2004;Lutz and Marsh 2007). Votes, however, are only an input to the determination of the policy-relevant outcomes of an election.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, researchers who have analyzed the potential impact of increased turnout have dealt solely with the effects on the distribution of votes; the results of these studies show that the potential impact of nonvoters is small (Lutz and Marsh 2007). However, the distribution of votes is only an input to the determination of the composition of the parliament, which in turn is an input to the process of government formation.…”
Section: List Of Tablesmentioning
confidence: 99%
“…The result of this poll was a narrow majority in support of the establishment of a new canton-51 percent voted yes, with 88 percent turnout! (turnout in Swiss referendums is normally below 50 percent) (Lutz and Marsh 2007). However, the referendum showed a split between the French-speaking Protestants in the southern part of Jura, who wanted to remain part of Bern.…”
Section: Box 3 the Establishment Of The Swiss Canton Of Jura In The mentioning
confidence: 99%